Influence of insecticide spraying regimes and cultivar on insect pests and yield of cowpea in the dry savannas of northeastern Nigeria - Kamara, Y.; Chikoye, David; Omoigui, L.O.; Dugje, I.Y. (2007)
Cowpea is an important food legume and versatile crop in the savannas of northeast Nigeria. Despite the high potential for production in this region, insect pests are a major constraint. A study was conducted to evaluate the response of diverse cowpea genotypes to different schedules of spraying with an insecticide. The study revealed that flower thrips, the legume pod borer (Maruca) and a range of pod-sucking bugs were the major insect pests. Application of insecticides once at flowering increased grain yield by 75%; application at both at flowering and podding , significantly reduced insect pest population and increased grain yield by 126%. Improved cultivars recorded a higher grain yield than the local checks at all spraying regimes. This suggests that these cultivars were either tolerant or resistant to the insect pests.